2017
DOI: 10.1155/2017/7502610
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Extract of Saraca indica Leaves in the Synthesis of Copper Oxide Nanoparticles: Finding a Way towards Going Green

Abstract: The present study is mainly aimed at the synthesis of copper oxide nanoparticles of varied size by green synthetic approach. The structural and morphological behavior of as-synthesized CuO nanoparticles were investigated using ultraviolet-visible spectral studies (UV-Vis), Fourier transform-Infrared spectroscopy (FT-IR), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy (EDX), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), transmission electron microscopy (TEM), and hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…The XRD pattern of biogenic CuO NPs is depicted in Figure 3. The presence of the quite clear and fairly sharp peaks with different 2θ values clearly demonstrated the highly crystalline structure of bio-assisted CuO nanopowder [34]. The analysis of assigned crystal planes (Bragg reflection) of rather strong peaks can be indexed to the monoclinic phase of CuO (JCPDS01-080-1268) [48].…”
Section: Xrd Examination Of Cuo Npsmentioning
confidence: 91%
See 1 more Smart Citation
“…The XRD pattern of biogenic CuO NPs is depicted in Figure 3. The presence of the quite clear and fairly sharp peaks with different 2θ values clearly demonstrated the highly crystalline structure of bio-assisted CuO nanopowder [34]. The analysis of assigned crystal planes (Bragg reflection) of rather strong peaks can be indexed to the monoclinic phase of CuO (JCPDS01-080-1268) [48].…”
Section: Xrd Examination Of Cuo Npsmentioning
confidence: 91%
“…There are a wide variety of traditional chemical and physical methods for CuO NPs fabrication including electrochemical methods [26], sonochemical [27], alcohothermal [28], hydrothermal decomposition [29], precipitation [30], polyol [31], and gamma radiation [32]. To avoid serious environmental hazards and health effects of chemical synthesis methods, several reports on phyto-assisted synthesis of CuO NPs by different parts of plant extracts have been published including abutilon indicum leaf [33], Saraca indica leaves [34], Rheum palmatum L. root [35], Aglaia elaeagnoidea flower [36], Malus domestica leaf [37], and green pea [38].…”
Section: Introductionmentioning
confidence: 99%
“…e pure anatase and Degussa P-25 TiO 2 used in this research are considered as direct band gap materials [57,58]. erefore, the value of n was taken 1/2 to plot the graph (αh]) 2 versus h] as shown in Figure 11. It is observed a reduction of 1 eV for the material Fe : Ti 0.1 in comparison with the pure TiO 2 (Fe : Ti 0) synthesized by the methodology of green chemistry assisted by ultrasound, which would allow to use more e ciently the solar radiation in heterogeneous photocatalytic processes for the degradation of organic pollutants.…”
Section: Uv-vis Drsmentioning
confidence: 99%
“…Solar energy is a renewable resource, and its efficient utilization in controlling environmental pollutions by using photocatalytic materials is one of the main goals of modern science and engineering [1][2][3][4]. Owing to exceptional and appropriate properties including nontoxic, excellent chemical stability, strong ultraviolet (UV) absorption, and wide band gap energy (anatase 3.2 eV and rutile 3.4 eV), titanium dioxide (TiO 2 ) is a recognized metal oxide semiconductor which could be extensively applied to diverse applications.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers conducted FTIR characterization techniques on the extract solutions and nanostructures which found that the reduction in the metallic ions resulted from phytochemicals such as phenols, flavones, terpenoids, proteins, and other heterocyclic compounds present during the reaction [ 78 , 79 , 80 , 81 ]. Copper-based nanomaterial studies also indicated initial aggregation of the particles that increased over time [ 82 , 83 ]. However, it was denoted that agglomeration may have been caused by an increase in catalytic activity on the surface of the nanoparticles, leading to the enhancement of its application [ 84 ].…”
Section: Green Synthesis Of Transitional Metals and Their Oxidesmentioning
confidence: 99%